Effects of Surface Oxide on the Nitridation Behavior of Aluminum Particles - Kim, Sung-Hoon; Noh, Jae-Hong; Ahn, Jae-Pyoung; Lee, Jae-Chul; Kwon, Hoon; Lee, Jaegab; Yang, Heang Ryeal; Lee, Kon-Bae (SPRINGER, 2015)
A detailed transmission electron microscopy study coupled with electron energy loss spectroscopy was conducted on AlN formed by the direct nitridation of Al particles under nitrogen atmosphere. The nitridation mechanism comprised two steps: the formation of AlN shell on Al particles and the growth of AlN with a lath type in Al droplets. Here, we found that the surface oxide layer of the Al particles acted as a channel layer, which supplied nitrogen in the atomic state to liquid Al, after being transformed into a thin AlON layer during the initial nitridation. In the Al particles, the inward growth of AlN with a shell structure occurred at the sub layer of the AlON layer. On the other hand, the extracted liquid Al droplets formed after the cracking of the AlN shell rested on the Al particles surrounded by the AlON layer. The nitridation of the droplets began at the interface between the Al particle and droplet and not at the free surface and grew outward from the droplet. Herein, based on the observation of the AlON layer formation, we propose a new mechanism for the nitridation of Al particles.
Keywords: ALN; ALLOYS; NITROGEN; SPECTROSCOPY; INFILTRATION; ATMOSPHERE; MECHANISMS; MAGNESIUM; COMPACTS; KINETICS